Healthy Living: Checking Blood Glucose - Jennifer Hillan; Linda B. Bobroff (EDIS)
Checking your blood glucose levels is an important part of managing diabetes. Your blood glucose values let you know how well your care plan is working and if you need to make any changes. This revised 3-page fact sheet was written by Jennifer Hillan and Linda B. Bobroff, and published by the UF Department of Family, Youth and Community Sciences, February 2015. (Photo iStock/Thinkstock.com)